In-Depth Understanding of Bullying in Schools: A Systematic Literature - Defriyanto, Defriyanto; Mulawarman, Mulawarman; Haryono, Haryono; Sunawan, Sunawan (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2024)
Bullying in schools is a pervasive issue with profound implications for students' academic performance and psychological well-being. This systematic literature review explores the complex dynamics of bullying, focusing on its contributing factors, impacts on academic outcomes, and preventive strategies. The review synthesizes findings from peer-reviewed studies published between [insert start date] and [insert end date], identified through searches in major academic databases including PubMed, PsycINFO, ERIC, and Google Scholar. Key themes include the role of individual traits, social dynamics, and environmental factors in shaping bullying behaviors. Factors such as peer pressure, family relationships, and school climate significantly influence the occurrence and severity of bullying incidents. The review highlights the detrimental effects of bullying on academic achievement, including reduced motivation, decreased concentration, and heightened psychological distress among victims. Effective prevention strategies discussed encompass proactive measures such as implementing anti-bullying policies, promoting positive peer relationships, and fostering empathy among students. School counselors and educators play pivotal roles in creating safe and inclusive environments through targeted interventions and support for victims. Challenges identified include variations in study methodologies and the need for culturally diverse perspectives in bullying research. Future research directions should prioritize investigating bullying across different cultural contexts and addressing emerging forms such as cyberbullying comprehensively. By advancing our understanding and implementing evidence-based interventions, we can work towards fostering inclusive school environments where all students feel safe, respected, and able to achieve their full academic potential